Legal and moral questions in contemporary Islamic banking and finance - Zakariyah, Luqman (2013)
As a result of the global financial recession, people have started to think about other ways to curb prevailing economic problems and the Islamic financial system has emerged as a possible, or potential solution to an obvious rescuer to the mayhem.